2012
DOI: 10.1128/jvi.06532-11
|View full text |Cite
|
Sign up to set email alerts
|

Prionemia and Leukocyte-Platelet-Associated Infectivity in Sheep Transmissible Spongiform Encephalopathy Models

Abstract: The dynamics of the circulation and distribution of transmissible spongiform encephalopathy (TSE) agents in the blood of infected individuals remain largely unknown. This clearly limits the understanding of the role of blood in TSE pathogenesis and the development of a reliable TSE blood detection assay. Using two distinct sheep scrapie models and blood transfusion, this work demonstrates the occurrence of a very early and persistent prionemia. This ability to transmit disease by blood transfusion was correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 40 publications
4
90
0
Order By: Relevance
“…Collectively, these studies revealed that prion infectivity titres of blood samples harvested during the asymptomatic phase of prion disease were up to 10-fold less than those collected during the clinical phase [10,19,20,22]. Infectious prions were found to be associated with white and red blood cells, platelets and plasma, although interspecies variations existed with regard to the distribution of prion infectivity in these different blood fractions [10,[15][16][17][18][19][20][21]. Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Collectively, these studies revealed that prion infectivity titres of blood samples harvested during the asymptomatic phase of prion disease were up to 10-fold less than those collected during the clinical phase [10,19,20,22]. Infectious prions were found to be associated with white and red blood cells, platelets and plasma, although interspecies variations existed with regard to the distribution of prion infectivity in these different blood fractions [10,[15][16][17][18][19][20][21]. Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20].…”
Section: Introductionmentioning
confidence: 92%
“…Infectious prions were found to be associated with white and red blood cells, platelets and plasma, although interspecies variations existed with regard to the distribution of prion infectivity in these different blood fractions [10,[15][16][17][18][19][20][21]. Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20]. These experimental transfusion studies have confirmed that all blood fractions prepared by protocols similar to those used in transfusion medicine can transmit prion disease [23,24].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations